The Relationship between Health Belief Model Applications with Smoking Quitting Behavior: A Meta-Analysis - Gadis Nur Anggreani; Faridah Nurhayati; Herawati Prianggi (Journal of Health Promotion and Behavior, 2022)
Background: Smoking is a habit of smoking cigarettes that is carried out in daily life, cigarettes are also a necessity that cannot be avoided for people who have a tendency to cigarettes. HBM is a model of individual health beliefs in determining the actions to be taken and is explained as a concept formulated with the aim of understanding why individuals do or do not perform various healthy behaviors. Therefore, this study aimed to determine the level of effectiveness of the Health Believe Model (HBM) application in the decision to quit smoking.Subjects and Method: This article was compiled with a systematic review and meta-analysis study. This study uses the PICO Model. The meta-analysis study was conducted by searching for articles from databases in electronic form including PubMed, Springer Link, Elsevier and Google Scholar. "Health Belief Model Application", or "Quit Smoking Behavior" or "Perceived Susceptibility" and "Perceived Severity". The inclusion criteria for this study were full articles using a cross-sectional study, with the publication year 2014-2021. Analysis of articles in this study using RevMan 5.3 . software.Results: A total of 12 cross-sectional studies from Asia, and Africa were selected for systematic review and meta-analysis.  The data collected showed that high perceived vulnerability increase 2.11 times to smoking quitting behavior compared with low perceived vulnerability, but its statistically not significant (OR= 2.09; 95% CI= 0.81 to 5.37; p= 0.130), and high perceived severity increase 1.43 times to smoking quitting behavior compared with low perceived severity (OR= 1.43; 95% CI= 0.57 to 3.58; p= 0.450), increase 2.11 times to smoking quitting behavior compared with low perceived vulnerability, but iw was statistically not significant.Conclusion: Perceived vulnerability, and perceived severity was not statistically significant in smoking quitting behavior.Keywords: health belief model, smoking qutting behavior, perceived vulnerability, perceived severity.Correspondence:Gadis Nur Anggreani. Study Program of Public Health, Universitas Tadulako, Palu, Central Sulawesi. Email: anggreanigadis@gmail.com.  Mobile: +6281335205131.Journal of Health Promotion and Behavior (2022), 07(03): 170-181DOI: https://doi.org/10.26911/thejhpb.2022.07.03.01